Lessons from Russia's Operations in Crimea and Eastern Ukraine. - Kofman, Michael (RAND Corporation, 2017)
This report assesses the annexation of Crimea by Russia (February-March 2014) and the early phases of political mobilization and combat operations in Eastern Ukraine (late February-late May 2014). It examines Russia's approach, draws inferences from Moscow's intentions, and evaluates the likelihood of such methods being used again elsewhere. These two distinct campaigns overlap somewhat but offer different lessons for participants and observers. The report finds that Russia's operation to annex Crimea represented a decisive and competent use of military force in pursuit of political ends. Russia's operations in Crimea benefited from highly favorable circumstances--political, historical, geographical, and military--that limit their generalizability. Analysis of the operation underscores that there are many remaining unknowns about Russia's military capabilities, especially in the aftermath of its military reforms and modernization program. The report also finds that the campaign in Eastern Ukraine was an ineffectually implemented--and perhaps ill-conceived--effort to achieve political fragmentation of Ukraine via federalization and retain Russian influence. Russia achieved its primary objectives but at a much higher cost than desired and through a fitful cycle of adaptation. This study thus questions the desirability for Moscow to replicate a course of events similar to the campaign in Eastern Ukraine. Conversely, the operation to annex Crimea was a highly successful employment of select elements within Russia's armed forces, making it an attractive use of military power, but the structural and operation factors contributing to its success raise doubts whether it can be repeated elsewhere.
Keywords: Russo-Ukrainian War, 2014-; Crimea (Ukraine) -- History, Military -- 21st century.; Russia (Federation) -- Relations -- Ukraine.; Russia (Federation) -- History, Military -- 21st century.; Ukraine -- Relations -- Russia (Federation); Frozen conflicts.; Grey areas.; Territorial disputes.; Guerre russo-ukrainienne, 2014-; HISTORY -- Europe -- Eastern.; HISTORY -- Europe -- Former Soviet Republics.; HISTORY -- Europe -- Russia & the Former Soviet Union.; International relations; Russia; Russia (Federation); Ukraine; Ukraine -- Crimea; Russian Federation.; Ukraine.; Crimea.; Annexation.; Armed forces.; International relations.; 2000-2099; Military history